Confiner les marges, marginaliser les confins : la souffrance des oubliés du lockdown dans les villes indiennes - Rémi de Bercegol; Anthony Goreau-Ponceaud; Shankare Gowda; Antony Raj (EchoGéo)
In India, on March 24, 2020 at 8:00 pm, the sudden announcement by the Prime Minister of the implementation of containment 4 hours later caused a strong panic among the underprivileged populations. Dramatic images of migrant workers desperately fleeing the big cities to return home have circulated around the world. But not all of them left, far from it, and many had no choice other than to remain confined to the margins. Through various testimonies gathered during the first three weeks of the lockdown in India, this article focuses on the very harsh conditions of confinement of poor populations, whose relegation to the margins was further reinforced by the crisis. In addition to the fact that the protective measures against the virus are impossible to respect there, due to promiscuity and insufficient access to water, the brutal disappearance of everyday livelihood strongly aggravates the low standard of living of the inhabitants. By revealing the paradoxical effects of a confinement that is not adapted to poor neighbourhoods, this article argues for a better consideration of the latter, during and after the pandemic crisis.